Dichromothrips corbetti (Priesner, 1936) (Thysanoptera: Thripidae): uma nova praga quarentenária em orquídeas no Brasil - Cavalleri, Adriano; Alves, Rogério M. de O.; Fabrício B. Lima, Élison (Entomological Communications, 2020)
Dichromothrips corbetti (Priesner, 1936) (Thysanoptera: Thripidae): a new quarantine pest in orchids in Brazil Dichromothrips corbetti (Priesner, 1936), listed as quarantine pest by the Brazilian Ministry of Agriculture, is recorded for the first time in Brazil. Specimens were first detected in the state of Bahia causing chlorosis and deformation on leaves, flowers and flower buds of Vanda and Mokara and Aranda orchids. This thrips species is native to Southeast Asia, but widely reported in countries of Europe and Oceania. This is the first record of D. corbetti in South America.